2015
DOI: 10.1016/j.jcma.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin expression in mouse Leydig cells correlates with age

Abstract: Our results suggest that kisspeptin10 does not affect steroidogenesis in adult Leydig cells, but its pattern of expression follows the stages of testicular development. Future studies should determine if kisspeptin regulates testicular development during puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…KISS1R localisation was not reported. In contrast, Wang et al [42] observed both KISS1 and KISS1R expression in adult mouse Leydig cells.…”
Section: Distribution Of Kisspeptin and Its Receptormentioning
confidence: 80%
See 2 more Smart Citations
“…KISS1R localisation was not reported. In contrast, Wang et al [42] observed both KISS1 and KISS1R expression in adult mouse Leydig cells.…”
Section: Distribution Of Kisspeptin and Its Receptormentioning
confidence: 80%
“…Some of these differences observed may be due to variation between species, age differences within the species and the different experimental methods employed [45]. [12,[19][20][21]42], round [12], and elongated spermatids [20]. • KISS1: primordial germ cells [19], and epididymal epithelium [20].…”
Section: Distribution Of Kisspeptin and Its Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the existence of mutual enhancement between kisspeptin and estradiol may be suggested since Kp-10 increases the expression of ERα/ß and 17β-estradiol increases the expression rate of Gpr54 [19][20] (Figure 2). Similarly than frog, also in mouse the expression profile of kiss1 and ERα fully parallel during postnatal testis development [16]. Consistently, in hypothalamic GT1-7 cell lines kisspeptin induces the expression of ERα and ERβ, whereas estradiol induces that of Gpr54 [22].…”
mentioning
confidence: 67%
“…Besides local kisspeptin activity, the secretion of kisspeptin produced by testis has been recently demonstrated in mouse [14]. However, beside the localization and the aforementioned observations, in testis explants and in immortalized or primary Leydig cell culture kisspeptin does not affect steroid biosynthesis [15][16]. By contrast, in rhesus monkey direct effect on testosterone biosynthesis has been demonstrated [17].…”
mentioning
confidence: 99%